The Correlation between Nutritional and Hydration Status with Physical Fitness in Young Soccer Athletes - Aviani Harfika; Fazlurrahman Hidayat (Journal of Applied Food and Nutrition, 2022)
Introduction: Soccer is a sport that is required optimal physical fitness. Previous studies have shown that nutritional status and hydration status affect the physical fitness of athletes. Malnutrition will affect physical fitness to be low while dehydration can increase fatigue in athletes and affect performance. The aim of this study was to determine the correlation between nutritional status and hydration status with physical fitness in young soccer athletes.Methods: This research is a cross-sectional study conducted on young soccer athletes from the Indonesian Football Association in Subang Regency (Persikas Subang). Subjects total of 28 people met the inclusion and exclusion criteria. Statistics were tested by using the Spearman correlation for the bivariate test.Results: Most of the subjects (85.7%) were in the normal nutritional status category, 64.3% in the mild dehydration, and 71.4% in the moderate physical fitness. There was a significant correlation between nutritional status and physical fitness (P0.05), but there was no significant correlation to hydration status. The results of the study concluded that nutritional status had a significant relationship with physical fitness.Discussions: This suggested that young soccer players could be aware of their nutritional status and fluid intake.